Illustrating Animals and Visualizing Natural History in Chambers’s Encyclopaedias - Rose Roberto (Cahiers Victoriens et Edouardiens)
In the 19th century, there was wide-spread public interest in natural history, as reflected in the high attendance at zoos and travelling menageries, in the market for popular field guides, in fashions for orchid collecting, fossil hunting and aquarium building, and in well-attended popular science lectures. More than 10 years before Darwin’s Origin of Species, a book titled Vestiges of the Natural History of Creation about evolution or ‘transmutation’ was anonymously authored by Scottish publisher Robert Chambers. The first edition sold out on both sides of the Atlantic. Chambers never admitted authorship of this book in his lifetime. His firm, W. & R. Chambers was well known for educational publishing. Between 1859 and 1892, the firm produced two encyclopaedias: Chambers’s Encyclopaedia: A Dictionary of Universal Knowledge for the People and Chambers’s Encyclopaedia: A Dictionary of Universal Knowledge, New Edition. Both editions contain numerous entries on mammals, birds, reptiles, fish, and microorganisms, with numerous illustrations depicting these topics. This paper discusses preliminary research on these encyclopaedias and the woodblocks used to illustrate them. It will discuss the depiction of animals and other natural history topics, comparing how entries and representations evolved between both editions and examine the influence of wider trends in the growing ‘popular markets’ for natural history, encyclopaedias, and book illustration generally during this period. Finally it looks at the firm’s philosophy of self-improvement, progress and understanding of science and questions whether the natural history images used in these encyclopaedias provided its 19th century audiences with any clues for the sensational author of Vestiges.